Fatty acid and carbohydrate metabolism in acute myocardial ischemia - M. A. Aripov; D. Kh. Kamardinov; S. V. Madoyan (Кардиоваскулярная терапия и профилактика, 2005)
Fatty acid metabolism (FA) requires 60-70% of O2 coming to myocardium. In O2 deficit, FA and carbohydrate metabolism declines. Reversible and irreversible ischemic damage is caused by unoxydated metabolites’ storage. Medicament therapy-induced carbohydrate metabolism is perspective, due to its less O2 demand.